Model Perlindungan Hukum terhadap Hak-Hak Masyarakat Kurang dan Tidak Mampu (MKTM) dalam Mendapatkan Pelayanan Kesehatan pada Rumah Sakit Umum Daerah (Rsud) Se-Eks Karesidenan Besuki - Dyah Ochtorina Susanti (JURNAL RECHTENS, 2015)
This study aims to find and analyze and provide an evaluation of the form of legal protection of the rights of the poor and can not afford (MKTM) in getting health care in general hospitals in the District of ex-Besuki, as well as to identify and analyze the general hospital faces and provide related solutions such constraints. The research results using qualitative research methods in particular in the form of case studies and field research (socio-legal) explains that this form of protection of the rights of the poor and can not afford (MKTM) in getting health care in general hospital in the district of ex- Besuki is in the form of services as stipulated in the Act and regulations set by each local government. Constraints in the delivery of health services is also a right of MKTM is the existence of human resources in the health sector (medical personnel) in each of the districts is still limited, in addition to the facilities (equipment) still terbats health so that not all patients are handled in hospital concerned. Related to this, if the hospital is not able to handle the patient, it will be referred to the hospital with more sophisticated tools.